A neuroimaging study in childhood autism - Mullick, Mohammad S. I.; Rahman, Wasima; Alim, S. M. Abu Hena Mostafa; Chowdhury, Hafizur Rahman (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Childhood autism is now widely viewed as being of developmental neurological origin. Abnormality in neuroimaging is reported in autism. Objectives: To delineate the proportion of structural magnetic resonance imaging (MRI) and electro encephalography (EEG) abnormality among the children with Autism and to assess any association of MRI and EEG changes with co morbid mental illness. Methods: It was a cross sectional descriptive study done at a child and adolescent consultation centre, Dhaka. The study was Carried out from January 2009 to December 2009. Both boys and girls were included in the study. A total of 42 children with childhood autism aged between two and 12 years participated in this study. Diagnosis of autism was based on ICD-10(DCR) criteria. Results: Abnormalities were found to be 35.7% in MRI and 42.9% in EEG. EEG abnormalities were found in the form of defuse slow waves activities, generalized faster activities, epileptogenic discharge and mixed discharge. The abnormalities in MRI was found in the form of diffuse cortical atrophic changes, focal cortical atrophy in frontal and temporal cortex with widening of major sulci, prominent ventricles, periventricular degeneration and abnormal basal ganglia. EEG changes were significantly associated with increased number of co-morbid illness (mental retardation, epilepsy and others). Conclusion: A number of abnom1alities that observed in the present study indicative of relations between structural and physiological dysfunctions and childhood autism. Further exploratory and in-depth researches are certainly required in this field. Intervention of autism needs to address co morbidities for better outcome.